Youtube Use As Media In Takallum (Arabic-Speaking) Learning Based On Project-Based Learning At Universitas Pendidikan Indonesia - Nurmala, Mia; Rosyidi, Abdul Wahab; Machmudah, Umi; Sodik, Achmad Ja’far; Fadhilah, Nurul (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2025)
This study aims to reveal Hiwar learning with YouTube media and its implementation in a project-based learning model. Arabic language learning activities in higher education cannot separate from using various media, including social media. YouTube is one of the largest platforms in the world, which is present in learning. In improving Arabic speaking skills, YouTube is a learning medium by presenting audio and video from Arabic origins. Also, involving students in language projects leads them to acquire speaking skills. This study used a qualitative approach with an exploratory case study method. The researcher carried out data collection through observation, interviews and documentation. The sampling technique used is the purposive sampling technique. The study results show that teaching human life in higher education uses YouTube as a learning medium. From this media, it can be found that audio and video of Arabic identity influenced student conversation skills. Students also get a variety of new vocabulary related to their daily activities. Another finding in hiwar learning is that the lecturer uses a project- based learning model in the form of Arabic-language masrahiyah in class. Before presenting masrahiyah, students choose a theme and produce a narrative text for masrahiyah.